2019
DOI: 10.1101/534818
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Population history and gene divergence in Native Mexicans inferred from 76 human exomes

Abstract: Native American genetic variation remains underrepresented in most catalogs of human genome sequencing data. Previous genotyping efforts have revealed that Mexico's indigenous population is highly differentiated and substructured, thus potentially harboring higher proportions of private genetic variants of functional and biomedical relevance. Here we have targeted the coding fraction of the genome and characterized its full site frequency spectrum by sequencing 76 exomes from five indigenous populations across… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
23
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 60 publications
12
23
1
Order By: Relevance
“…Such a fragmented demographic history of Mexican groups was proposed also by previous studies, which pointed to a genetic structure of Native Mexicans that is more related to their territories' orography rather than to cultural/linguistic differences (Gorostiza et al 2012;González-Martín and Gorostiza 2013;Moreno-Estrada et al 2014;Rangel-Villalobos et al 2016). In particular, our findings are consistent with results from the analysis of exome sequence data of Mexican indigenous populations, including TAR, HUI, TRQ and MYA, which inferred that northern and southern ancestral Native Mexican groups split approximately 7.2 thousand years ago (KYA) and further diverged locally around 6.5 and 5.7 KYA, respectively (Ávila-Arcos et al 2020). Moreover, more recent differentiation between HUI/PUR (3.4 KYA), NAH/PUR (2.2 KYA), and HUI/NAH (357 YA) seems to support our assumption that these CMC populations largely shared a common evolutionary history since they diverged from NMC and SMC groups (González-Martín and Gorostiza 2013).…”
Section: Fine-scale Genetic Structure Of Native Mexican Populationssupporting
confidence: 88%
See 3 more Smart Citations
“…Such a fragmented demographic history of Mexican groups was proposed also by previous studies, which pointed to a genetic structure of Native Mexicans that is more related to their territories' orography rather than to cultural/linguistic differences (Gorostiza et al 2012;González-Martín and Gorostiza 2013;Moreno-Estrada et al 2014;Rangel-Villalobos et al 2016). In particular, our findings are consistent with results from the analysis of exome sequence data of Mexican indigenous populations, including TAR, HUI, TRQ and MYA, which inferred that northern and southern ancestral Native Mexican groups split approximately 7.2 thousand years ago (KYA) and further diverged locally around 6.5 and 5.7 KYA, respectively (Ávila-Arcos et al 2020). Moreover, more recent differentiation between HUI/PUR (3.4 KYA), NAH/PUR (2.2 KYA), and HUI/NAH (357 YA) seems to support our assumption that these CMC populations largely shared a common evolutionary history since they diverged from NMC and SMC groups (González-Martín and Gorostiza 2013).…”
Section: Fine-scale Genetic Structure Of Native Mexican Populationssupporting
confidence: 88%
“…Admixed) individuals, in whom the effects of recent ecological transitions and Westernization of lifestyles have been predominantly investigated (Rivera et al 2004;Aguilar-Salinas et al 2011;Weissglas-Volkov et al 2013;Ko et al 2014).Conversely, few studies have focused so far on Native Mexican populations (Acuña-Alonzo et al 2010; Lara-Riegos et al 2015;Romero-Hidalgo et al 2017), who are instead the most suitable groups to be considered for inferring the pre-Columbian evolutionary history of the ancestors of modern Mexican people (Moreno-Estrada et al 2014;Ávila-Arcos et al 2020). Interestingly, these studies revealed a complex genetic structure of the main indigenous groups that have long-inhabited the present-day Mexico's territory, which is tightly related to the well-known historical, cultural and demographic processes they have experienced (Moreno-Estrada et al 2014;Romero-Hidalgo et al 2017;Ávila-Arcos et al 2020). In particular, a northwest-southeast gradient of Mexican variation has been described, along with an overall differentiation in the proportions of ancestry components between northern, central and southern populations, which is clearly distinguishable in both Native and geographically-neighboring Mexican Mestizo groups (Rubi-Castellanos et al 2009;Moreno-Estrada et al 2014).Major genetic divergence between Aridoamerican (i.e.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, in our subsample, the highest proportion of short stature women was found among indigenous women, which may further aggravate child stunting outcomes. Recent genetic analyses have identified idiopathic short stature among the Mexican indigenous population across generations [ 36 ]. While this trait may partially explain offspring’s short stature in this population, it does not fully account for the persistence of the intergenerational effect of undernutrition and its negative cognitive and developmental outcomes, which continue to be pervasive in this group in Mexico.…”
Section: Discussionmentioning
confidence: 99%